2004
DOI: 10.1097/01.nmd.0000138227.25832.e7
|View full text |Cite
|
Sign up to set email alerts
|

Depression With Versus Without Manic Features in Rapid-Cycling Bipolar Disorder

Abstract: Depression has been identified as a hallmark feature of rapid-cycling bipolar disorder, although less attention has been paid to the presence of manic features accompanying depression in rapid cyclers. To provide greater information about the extent to which depression arises with or without salient manic features in rapid cycling, we conducted a preliminary study of rapid cycling in outpatients seeking treatment at an academic specialty center for bipolar disorder. Forty DSM-IV affectively symptomatic bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…Whatsoever, there was a correlation between the age of onset and severity of current Recent literature suggests that mixed states and agitated depression are clinical features closely associated with RC course in BD patients. 9,28,46,47 In line with this, we found that BD-RC patients presented a higher prevalence of hypomanic/manic symptoms such as irritable mood, risky behavior, impulsivity, and psychomotor agitation (Table 2). Agitation, in particular, has been reported to be very frequent in mixed states 48 and may be a major cause of complications and challenges for the therapeutic Alliance.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Whatsoever, there was a correlation between the age of onset and severity of current Recent literature suggests that mixed states and agitated depression are clinical features closely associated with RC course in BD patients. 9,28,46,47 In line with this, we found that BD-RC patients presented a higher prevalence of hypomanic/manic symptoms such as irritable mood, risky behavior, impulsivity, and psychomotor agitation (Table 2). Agitation, in particular, has been reported to be very frequent in mixed states 48 and may be a major cause of complications and challenges for the therapeutic Alliance.…”
Section: Discussionsupporting
confidence: 66%
“…7,19,23,24 Furthermore, other studies highlight the prominence of depressive episode in association with manic features, rather than depressive symptoms alone in a substantial proportion of patients with RC. [25][26][27][28] The co-occurrence of mixed features and RC in patients with BD has been associated with a worse response to treatment. 7,29 Data concerning pharmacological management of RC are still sparse, 10 partially due to the fact that RC patients are often excluded from controlled treatment trials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research using life charting of mood symptoms has shown that depressive episodes or subsyndromal depressive symptoms not only dominate the course of illness of persons seeking treatment for bipolar I and II disorders (118, 119), but also frequently co‐occur or rapidly alternate with manic and hypomanic symptoms to form various types of mixed and rapid‐cycling affective states (76, 78). Such states include mixed mania, mixed hypomania, mixed depression, agitated depression, ultra‐rapid cycling and rapid mood switching (65–69, 75–81, 120–126). Although the precise nosological boundaries of these mood states are an active area of research, an increasing number of empirical studies have shown that these mixed states are often associated with suicidality.…”
Section: Factors Associated With Suicidality In Bipolar Disordermentioning
confidence: 99%
“…In addition, several studies have shown mixed mania – syndromal mania associated with prominent or syndromal depression – to be associated with greater suicidality than pure mania (79–81, 120). Perhaps more importantly, a growing number of studies have shown that depressive mixed states – syndromal major depression associated with hypomanic or manic symptoms (but not a manic syndrome) – may similarly be characterized by more suicidal thoughts or behaviors than pure or simple depressive states (i.e., major depression without hypomanic features) (69, 77, 123).…”
Section: Factors Associated With Suicidality In Bipolar Disordermentioning
confidence: 99%
“…In general, RCBD has been associated with worse disease outcome 9,10 and more severe disability. 7,11,12 More specifically, many factors have been described to be associated with RC, such as female gender, 5,13 earlier age at onset, 6,12 increased risk for suicide, 13,14 predominance of depression, 15,16 hypothyroidism, 6,17 bipolar type II disorder, 8,18,19 and higher rates of antidepressants use. 7,20 However, some of these associations are still controversial, and many studies have been criticized regarding aspects such as lack of a uniform definition of RC and use of heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%